2014
DOI: 10.1186/1471-2431-14-160
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal mortality in pregnancies with omphalocele: data from the Chinese national birth defects monitoring network, 1996–2006

Abstract: BackgroundPrevious studies on the mortality rate of omphalocele are limited. The risk of death of non-isolated omphalocele and that of cases of omphalocele that are diagnosed prenatally by ultrasound are unclear. This study aimed to estimate the perinatal mortality of pregnancies with omphalocele. This study also examined the potential risk of death of non-isolated omphalocele and that of cases that are prenatally diagnosed by ultrasound.MethodsData were retrieved from the national birth defects registry in Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 24 publications
2
14
0
2
Order By: Relevance
“…19 Neonatal lethality for gastroschisis, omphalocele and esophageal atresia observed in other investigations was generally below the rates observed in our study. [20][21][22] Consistent with our work, several studies have associated prematurity to a higher mortality rate among infants affected with selected CAs. 18,20,[23][24][25] However, some investigations conducted in gastroschisis patients have demonstrated that elective preterm C-sections prevented the occurrence of intestinal inflammation and improved enteral functioning because the exposure time of bowel loops to amniotic fluid meconium was shorter.…”
Section: Discussionsupporting
confidence: 79%
“…19 Neonatal lethality for gastroschisis, omphalocele and esophageal atresia observed in other investigations was generally below the rates observed in our study. [20][21][22] Consistent with our work, several studies have associated prematurity to a higher mortality rate among infants affected with selected CAs. 18,20,[23][24][25] However, some investigations conducted in gastroschisis patients have demonstrated that elective preterm C-sections prevented the occurrence of intestinal inflammation and improved enteral functioning because the exposure time of bowel loops to amniotic fluid meconium was shorter.…”
Section: Discussionsupporting
confidence: 79%
“…19 La letalidad neonatal en gastrosquisis, onfalocele y atresia esofágica observada en otras investigaciones ha estado, en general, por debajo de las cifras observadas en nuestro estudio. [20][21][22] Concordante con nuestro estudio, la prematurez ha sido asociada en varios trabajos a una mayor tasa de mortalidad en afectados con las AC seleccionadas. 18,20,[23][24][25] Sin embargo, algunas investigaciones realizadas en pacientes con gastrosquisis han mostrado que las cesáreas electivas pretérmino evitaron la aparición de daño inflamatorio intestinal y mejoraron el funcionamiento enteral por presentar menor tiempo de exposición de las asas al meconio del líquido amniótico.…”
Section: Discussionunclassified
“…Pre-and perinatal mortality is high in omphalocele. A large cohort study revealed that 37% of the cases had termination of pregnancy or stillbirth, an additionally 15% died within the first 15 days after delivery, and that prenatally diagnosed and non-isolated omphaloceles had a significant higher mortality than postnatally diagnosed and isolated cases [41].…”
Section: Prenatal Diagnosis and Carementioning
confidence: 99%